2007
DOI: 10.1007/bf02912893
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic and hepatoprotective effects of flaxseed chutney: Evidence from animal studies

Abstract: Rats fed with hypercholesterolemic diet showed a significant increase in serum total -cholesterol, liver homogenate total -cholesterol, HDL-cholesterol and changed LDL-cholesterol, and HDL/LDL ratio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
4
16
1
Order By: Relevance
“…It is known that the leakage of these intracellular hepatic enzymes into the blood stream is an indicator of hepatic cells damage frequently related to the susceptibility of their walls to oxidative stress (Das et al, 2010). Our findings are consolidated by previous studies in which flaxseed chutney has demonstrated a hepatoprotective function by decreasing liver marker enzymes GOT, GPT and ALP in the serum (Shakir and Madhusudhan, 2007a). Moreover, flax addition to the diet of rats exposed for a long-term to azoximethane, results in a significant decrease in liver -glutamyl transpeptidase profile and liver lipids and micronuclei formation (Shakir and Madhusudhan, 2007b).…”
Section: Blood Parameterssupporting
confidence: 68%
“…It is known that the leakage of these intracellular hepatic enzymes into the blood stream is an indicator of hepatic cells damage frequently related to the susceptibility of their walls to oxidative stress (Das et al, 2010). Our findings are consolidated by previous studies in which flaxseed chutney has demonstrated a hepatoprotective function by decreasing liver marker enzymes GOT, GPT and ALP in the serum (Shakir and Madhusudhan, 2007a). Moreover, flax addition to the diet of rats exposed for a long-term to azoximethane, results in a significant decrease in liver -glutamyl transpeptidase profile and liver lipids and micronuclei formation (Shakir and Madhusudhan, 2007b).…”
Section: Blood Parameterssupporting
confidence: 68%
“…A study on hypercholesterolemic rats fed on flaxseed chutney supplemented diet (15 %) revealed significant reduction in LDL cholesterol and total serum cholesterol and no change in HDL cholesterol. In CCl 4 intoxicated rats, lipid peroxidation products were neutralized by flaxseed lignans (Shakir and Madhusudan 2007). Several clinical studies showed that EPA and DHA play a major role in reducing depression symptoms.…”
Section: Metabolismmentioning
confidence: 99%
“…It is interesting to know that flaxseed was native of India and was a staple food crop. In India, flaxseed is still being consumed as food and as well as for medicinal purposes (Shakir and Madhusudan 2007). It enjoys a good status among oilseeds because of its versatile uses.…”
Section: Introductionmentioning
confidence: 99%
“…flax seed chutney was able to lower the cholesterol levels and shown the antioxidant protective effect against the carbon tetrachlorideinduced hepatotoxic damage in rats [46]. To check the effects of linseed consumption on lipid profile in rabbits on a hypercholesterolemic diet, investigators conducted an experimental study involving a total of 20 adult male white rabbits that were divided into two groups, a control and an experimental group.…”
Section: Animal Studiesmentioning
confidence: 99%